Magneto-elastic coupled finite element analyses - Billardon, Rene; Hirsinger, Laurent; Ossart, Florence (European Journal of Computational Mechanics, 1999)
The aim of this paper is to introduce a general framework to model the coupled phenomena which occur when a system of solids is subjected to thermal, magnetic and mechanical loadings. This framework constitutes the basis of the numerical methods to be developed in order to perform coupled thermo-magneto-mechanical structural analyses of electrical machines. These general concepts are illustrated by different examples.